Dibalik Penetapan Peraturan Pembayaran Upah di Bawah Upah Minimum - Satrio Abdi Pangestu; Dipo Wahjoeono (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In this study, researchers used the title "Behind the Establishment of Regulations for Payment of Wages Below the Minimum Wage" with the aim of finding out the reasons behind the establishment of regulations that allow certain companies to pay workers wages under the provisions of the Law, namely the Minimum Wage. Using normative research methods, namely examining laws and regulations, legal understandings, or legal doctrines to be used in answering problem issues in this writing. This research uses legal, historical and conceptual approaches. Based on research, wages are rewards or payments that are the right of workers / workers and an obligation for companies / employers. The amount of the minimum wage has been determined by law which is the benchmark for employers in paying their workers. However, with the phenomenon of global economic changes, there are regulations that allow companies / employers to pay wages lower than the minimum wage. So why is this allowed, what factors make the regulation enacted. The results showed that the enactment of regulations that allow paying below the Minimum Wage was due to the impact of global economic changes supported by data stating that export activities in labor-intensive companies decreased drastically around 30%, which eventually became an urgency for the Government to overcome the problem.